2003
DOI: 10.1002/fld.492
|View full text |Cite
|
Sign up to set email alerts
|

A new hybrid turbulence modelling strategy for industrial CFD

Abstract: SUMMARYThis paper presents a new strategy for turbulence model employment with emphasis on the model's applicability for industrial computational uid dynamics (CFD). In the hybrid modelling strategy proposed here, the Reynolds stress and mean rate of strain tensors are coupled via Boussinesq's formula as in the standard k-model. However, the turbulent kinetic energy is calculated as the sum of the normal Reynolds-stress components, representing the solutions of the appropriate transport equations. The equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…However, so far Reynolds stress models have not been widely used in the engineering applications despite their theoretical superiority. A key shortcoming of the Reynolds stress models is their lack of stability and robustness, i.e., the difficulty in achieving convergence (Basara & Jakirlic 2003;Maduta & Jakirlic 2017) and the high sensitivity to the modeling of unclosed terms (particularly the pressure-rate-of-strain tensor) in the Reynolds stress transport equations.…”
Section: Introductionmentioning
confidence: 99%
“…However, so far Reynolds stress models have not been widely used in the engineering applications despite their theoretical superiority. A key shortcoming of the Reynolds stress models is their lack of stability and robustness, i.e., the difficulty in achieving convergence (Basara & Jakirlic 2003;Maduta & Jakirlic 2017) and the high sensitivity to the modeling of unclosed terms (particularly the pressure-rate-of-strain tensor) in the Reynolds stress transport equations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, after calculating SAE notchback reference body (Basara et al 2002), Ahmed Body (Basara and Jakirlic 2003) or Morel Body (Basara and Alajbegovic 1998) etc., the same procedure was applied for more complex models. Therefore, after calculating SAE notchback reference body (Basara et al 2002), Ahmed Body (Basara and Jakirlic 2003) or Morel Body (Basara and Alajbegovic 1998) etc., the same procedure was applied for more complex models.…”
Section: Resultsmentioning
confidence: 99%
“…4. The HTM approach was previously tested on many simple examples including all cases shown in the introduction (Basara and Jakirlic 2003). However, it was possible to perform such numerical study as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While the propagation of random eddy viscosity is straightforward and doesn't require modification of the solver in general, the propagation of random Reynolds stresses is numerically more challenging. To achieve numerically stable performance of the solver, we adopt a blending of the random Reynolds stress, which we wish to propagate, and a contribution based on the Boussinesq assumption [42]. While the latter alters the propagated effective Reynolds stress, it promotes numerical convergence of the solver.…”
Section: Mlmc-rans Implementationmentioning
confidence: 99%